A mixed relationship: bureaucracy and school performance - Smith, Kevin B.; Larimer, Christopher W. (2004)
We argue the negative relationship between school bureaucracy and school performance that is commonly reported in the bureaucracy and educational policy literature is theoretically and empirically incomplete. Like most public agencies operating in complex task environments, we suggest that schools have to make trade-offs between the multiple outputs they are expected to produce. Bureaucracy plays an important role in determining the nature of these trade-offs: one that is more multidimensional than it is portrayed in the existing literature. We find bureaucracy's relationship with school performance depends on how performance is measured. It is negatively associated with test scores but positively associated with other performance measures such as attendance and dropout rates. This is consistent with an economies-of-scope perspective of bureaucracy, which emphasizes bureaucracy's role in managing the trade-offs inherent in pursuing multiple goals. - Reproduced.
Keywords: Education; Schools; Bureaucracy